Measurement of the transverse momentum spectra of weak vector bosons produced in proton-proton collisions at √s=8 TeV - CMS, The CMS collaboration; Khachatryan, Vardan; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2017)
The transverse momentum spectra of weak vector bosons are measured in the CMS experiment at the LHC. The measurement uses a sample of proton-proton collisions at s=8 TeV, collected during a special low-luminosity running that corresponds to an integrated luminosity of 18.4 ± 0.5 pb−1. The production of W bosons is studied in both electron and muon decay modes, while the production of Z bosons is studied using only the dimuon decay channel. The ratios of W− to W+ and Z to W differential cross sections are also measured. The measured differential cross sections and ratios are compared with theoretical predictions up to next-to-next leading order in QCD.